IMPLEMENTASI TEKNOLOGI PENGINDERAAN JAUH BERBASISDUAL DOPPLER RADAR SEBAGAI UPAYA MITIGASI ASAP KARHUTLA - Rosyady, Muhammad Panji; Saputra, Agung Hari; Pangestu, Titis Angger; Putri, Ashifa (Pusdiklat BMKG, 2020)
During 2018, forest and land fires that occurred in the Banjarbaru area were recorded to the tune of 98,637hectares. The incident caused in the occurrence of smog that could harm the environment and human health. Direct and continuous monitoring of haze is needed by the community and government in providing early warning information related to haze of forest and land fires. Detection of haze from forest and land fires can be done by one of the remote sensing system, called the weather radar. However, for the detection of smoke haze from forestand land fires using weather radar is necessary to pay attention to the quality of radar data and the range of observations. Therefore, to improve the quality of weather radar data, clutter correction is used. In addition, it also can be used dual doppler method to increase the range of detection when smoke haze happen. This research was conducted on 12, 17 and 27 September 2018 in the Banjarbaru area using weather radar data, ME48 data, and hotspot data. This study aims to determine the application of the dual doppler method as well as the spatial and temporal characteristics of land fire smoke distribution. The results showed that the minimum visibility reached 10 m at the time of the haze of forest and land fires. Observation of haze of forest and land fires usingweather radar indicates the presence of smoke echo with a reflectivity value of -6 - 13 dBZ with smoke height reaching 2 km with the direction of smoke distribution moving from southeast to northwest.